Inference of mixed information in Formal Concept Analysis - Mora-Bonilla, Ángel; Cordero-Ortega, Pablo; Enciso-García-Oliveros, Manuel; Rodríguez, Jose Manuel (My University, 2017)
Negative information can be considered twofold: by means of a negation operator or by capturing the absence of information. In this second approach, a new framework have to be developed: from the syntax to the semantics, including the management of such generalized knowledge representation. In this work we traverse all these issues in the framework of formal concept analysis, introducing a new set of inference rules to manage mixed (positive and negative) attributes.
Keywords: Lenguajes formales; Lógica simbólica y matemática; Logic; Formal concept Analysis